A roles-based approach to variable-oriented programming - Sorva, Juha (Human Technology, 2008)
Delocalized variable plans pose problems for novice programmers trying to read and write programs. Variable-oriented programming is a programming paradigm that emphasizes the importance of variable-related plans, and localizes actions pertaining to each variable together in one place in the program code. This paper revisits the idea of variable-oriented programming and shows how it can be founded on roles of variables: stereotypes of variable use suitable for teaching to novices. The paper sketches out how variable-oriented, roles-based programming could be implemented using either a new programming language or a framework built on an existing language. The possible applications, merits, and problems of a roles-based approach, and variable-oriented programming in general, are discussed. This paper points toward possible research directions for the future and provides a basis for further discussions of variable-oriented, roles-based programming.